Tingkat Kesadaran Multikultural Mahasiswa dan Urgensinya Bagi Bimbingan dan Konseling - Devi Permatasari; Khairul Bariyyah; Ch. Erghiezha Ninuk Indrati K. (Universitas Kanjuruhan Malang, 2016)
Multicultural awareness is the foundation of communication and it involves the ability of standing back from ourselves and becoming aware of our cultural values, beliefs and perceptions. Multicultural awareness becomes central when we have to interact with people from other cultures. People see, interpret and evaluate things in a different ways. What is considered an appropriate behavior in one culture is frequently inappropriate in another one.this research use descriptive- quantitative methodology to indentify level of students multicultural awareness specifically will be identified by gender and academic years. This research will identify multicultural awareness based on differences of gender, academic years. This research use random and purposive random sampling of 650 students from university. These studies identify of multicultural awareness 3% in high condition, 82,6 % medium, and 5,8% in low. Further, there is a significant difference in the level of multicultural awareness based on gender and academic year. These findings could not be generalized because of the limited sample and ethnicity; it should need a wider research so that can be generalized and recommended the efforts to development and improvement of multicultural awareness conditions for optimization the services. Keyword: Multicultural Awareness, Gender, Academic Years